Coordinated optimized scheduling of locks and transshipment in inland waterway transportation using binary NSGA‐II. (19th September 2019) - Ji, Bin; Sun, Hongjun; Yuan, Xiaohui; Yuan, Yanbin; Wang, Xiaorong
Abstract: Traffic congestion in inland waterways caused by insufficient throughput capacity of locks has become a compelling problem in developed inland shipping countries. In order to avoid excessive time wasted in waiting for lock service, it is suggested that some types of cargoes should be unloaded at the quays and transported by road/train to their destinations, which is called water–land transshipment. By this means, the ships are divided into two groups that either pass the lock or are transshipped at the quays, engendering the lock and water–land transshipment co‐scheduling (LWTC) problem. This paper focuses on the LWTC, where the roll‐on roll‐off ships, passenger ships, and general cargo ships that can be transshipped and other ships that can only pass the lock are considered in a lock‐quay co‐scheduling system. The LWTC problem is decomposed into an outer‐layer main 0‐1 optimization problem and two inner‐layer subproblems: lock scheduling and berth allocation. A multiobjective optimization model is proposed for the LWTC problem based on its two‐layer structure. To solve the LWTC problem, a hybrid heuristic method is proposed, where a modified binary nondominated sorting genetic algorithm II is proposed to solve the main problem, and the two subproblems are solved by specific heuristics. The proposed model and hybrid method are tested on instances extracted from historical data of traffic at Three Gorges Dam, the results of which demonstrate the feasibility of the model and the superiority of the proposed hybrid heuristic method over other comparisons.